Valor nutricional e características fermentativas da silagem de capim-mombaca com a adição de farelo de soja - Santos, Diogo Silva (2015)
We evaluated the effects of adding soybean meal (SM) as an additive sequestrant of moisture and nutrient source in mombasa grass silage, compared to standard fermentation and in situ degradability of silage with different levels of inclusion of soybean meal. The experiment was conducted at Fazenda AJR, in the municipality of Goiás, Goiás.The treatments used were composed of four levels of inclusion of SM 0%, 10%, 15% and 20%.The experimental design was completely randomized, with four treatments and four replicates.The mombasa grass featured 24.8% DM cutting time and was silage in silos, PVC minis closed during 65 days.After the opening of the minis silos were performed to determine the losses weighing through the quantification of effluent production and losses by gas.Samples were collected for further analysis of ammoniacal nitrogen, pH and soluble carbohydrates, as well as the chemical composition-mycotoxin (s), degradability in situ.The addition of the additive has increased the level of DM and was efficient in the control of effluents and gaseous losses.The additive allowed great recovery rates of DM.The addition of SM favored the increase of lactic, acetic acid and butyric acid and propionic concentrations, reflecting the improvement of the fermentation of silage profile.The addition of the SM has provided greater total carbohydrates content in all levels of inclusion.Silages containing SM had highercrude protein (CP) content, as well as lower fiber content in a neutral detergent (NDF) and acid detergent fiber (ADF).The degradability of the DM, NDF and CP improved linearly according to the addition of SM, reaching degradabilities potential and specific degradabilities best, with the inclusion of 20% of SM.The addition of soybean meal provided silage well preserved, with minimal loss of DM and still contributed significantly to the improvement of the nutritional value of silage.